STUDI AWAL PENGARUH JUMLAH SUDU TERHADAP DAYA KELUARAN TURBIN ANGIN TIPE HORIZONTAL BERDIAMETER 1,6 METER SEBAGAI SUMBER PENYEDIA LISTRIK PADA PROYEK RUMAH DC DI FMIPA UNJ - S, Puji; S, Satwiko; Taufik, Taufik (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2012)
With wind turbines, wind energy can be converted into electrical energy. In general, wind turbines typically use 3 blades, wind turbine is one source of electricity providers. Influence the number of blades on the output power generated by wind turbines of type horizontal diameter of 1.6 meters in DC home projects. Comparison of the energy efficiency of electricity generated from two identical wind turbine blade with a number of different variations. Keywords: Wind turbines, DC house, Efficiency.